Handbook of urban insects and arachnids - Robinson, William H., 1943- (Cambridge University Press, 2005)
William Robinson provides comprehensive coverage of the insect and other arthropod pests in the urban environment worldwide. Detailed information is presented on the development, habits, and distribution of urban and public health pests.